2010
DOI: 10.1007/s00401-010-0715-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-related motor neuron degeneration in DNA repair-deficient Ercc1 mice

Abstract: Degeneration of motor neurons contributes to senescence-associated loss of muscle function and underlies human neurodegenerative conditions such as amyotrophic lateral sclerosis and spinal muscular atrophy. The identification of genetic factors contributing to motor neuron vulnerability and degenerative phenotypes in vivo are therefore important for our understanding of the neuromuscular system in health and disease. Here, we analyzed neurodegenerative abnormalities in the spinal cord of progeroid Ercc1Δ/− mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 70 publications
5
112
1
1
Order By: Relevance
“…The upregulation of these classes of proteins marks an increased recruitment of astrocytes and/or other glial cells indicating an increase in neuronal damage and inflammation in the cerebellum of KO mice. This is in line with previous studies that have shown that aging and the lack of efficient DNA repair can trigger neurodegenerative and inflammatory processes (23,(25)(26)(27). Other proteins found to be up-regulated are extracellular proteins that are known to interact with or modify the extracellular environment (HTRA1 and Lama2) as well as cell adhesion molecules (PECAM-1 and MCAM).…”
Section: Resultssupporting
confidence: 91%
“…The upregulation of these classes of proteins marks an increased recruitment of astrocytes and/or other glial cells indicating an increase in neuronal damage and inflammation in the cerebellum of KO mice. This is in line with previous studies that have shown that aging and the lack of efficient DNA repair can trigger neurodegenerative and inflammatory processes (23,(25)(26)(27). Other proteins found to be up-regulated are extracellular proteins that are known to interact with or modify the extracellular environment (HTRA1 and Lama2) as well as cell adhesion molecules (PECAM-1 and MCAM).…”
Section: Resultssupporting
confidence: 91%
“…Macroscopically, the brains of Ercc1 ⌬/Ϫ mice are smaller, but proportional to their reduced body size (de Waard et al, 2010). The gross histological organization analyzed in thionine stained sections appeared normal in all brain areas, including hippocampus ( Fig.…”
Section: Ercc1mentioning
confidence: 96%
“…Consistently, ERCC1-deficient cells show increased sensitivity to agents or treatments that damage DNA, and hence it is expected that these animals accumulate DNA damage at a higher rate than control animals (Sijbers et al, 1996;Muñoz et al, 2005;Ahmad et al, 2008;Hoeijmakers, 2009). Recently it was shown that these animals have age-related neuronal changes in the spinal cord as well as in neuromuscular junctions of the skeletal muscle (de Waard et al, 2010). Here we show that global Ercc1 mutants as well as neuron-specific Ercc1 mutants exhibit an age-dependent decrease in neuronal plasticity, and progressive neuronal pathology, suggestive of neurodegenerative processes.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations